Hailey-Hailey disease associated with herpetic eczema-the value of the Tzanck smear test - Thomás de Aquino Paulo Filho; Yara Kelly Rodrigues de Freitas; Mylenne Torres Andrade da Nóbrega; Carlos Bruno Fernandes Lima; Barbara Luiza Medeiros Francelino Carriço; Maria Aurora Pinto Leite e Silva; Filipe Lauria Paulo; Pedro Bezerra da Trindade Neto (Mattioli1885, 2014)
Background: Herpetic eczema is a herpetic superinfection of a preexisting skin disease. Hailey-Hailey disease is an autosomal dominant dermatosis that is clinically characterized by flaccid vesicles and rashes in intertriginous areas. The coexistence of those findings is a rare condition; only five cases have been published in literature. Purpose: To report the rare coexistence between Hailey-Hailey disease and herpetic eczema and to highlight the importance of cytology for a quick diagnosis. Case report: A 38-year-old man had been diagnosed with Hailey-Hailey disease for 13 years. His condition evolved into what could be herpetic eczema, which was later confirmed by skin cytology and histopathology. The man showed remission in the infection after 10 days under treatment with acyclovir. Conclusion: Research on the concomitance of infection by the herpes virus must be performed in the exacerbations of Hailey-Hailey disease, and, in those situations, the quick diagnosis through skin cytology makes the early treatment possible.